The Patterns of Clinical Presentation in Patients with Unsafe Miscarriage - Khanum, Faiza; Tariq, Amera; Waseem, Syed Majid; Mahmood, Tariq (Pakistan Armed Forces Medical Journal, 2022)
Objective: To study the pattern of clinical presentation in patients with unsafe miscarriages. Study Design: Case series study. Place and Duration of Study: Department of Obstetrics and Gynaecology, Pak Emirates Military Hospital, Rawalpindi Pakistan, from Apr 2016 to Mar 2017. Methodology: Thirty patients were included in this study after approval of the Ethical Committee. Detailed clinical assessment and clinical presentations of the cases were noted. Methods of miscarriage and associated complications were also noted. All cases were unbooked and referred cases. Results: In this study, 30 patients with unsafe miscarriages were studied. The mean ages of the patients were 27.4±7.1 years. Most of the patients were married (93.3%, n=28,) multigravida (73.3%, n=22,) and in 1st trimester (76%, n=23). The method of the abortions was by instrumentations in 90%, (n=27) cases and vaginal tablets in only 10%(n=03) of the cases. The mean hospital delay was of 8.5±10.1 days. Abdominal pain was the commonest presentation in 90% of the patients (n=27). Acute abdomen with abdominal distension and constipation was seen in 53.3%(n=16) cases. There was a history of vaginal bleeding in 43.3%(n=13) cases, and 6.7% (n=2) of patients presented in shock. Mean vitals on admission were as pulse 108.7±13.4 per minute, temperature 99.4+2°F, respiratory rate 24.3±4 per minute, systolic and diastolic blood pressure were 103.5.5±14 mmHg and 68.6±10.4 mmHg respectively. Conclusion: Illegally induced abortion remains a prominent cause of maternal morbidity in our society. However, high-quality post-abortion care will help a long way in saving many lives.